Implementasi Pendidikan Karakter Religius di TK Al-Azam Semarang - Sukmawati, Endah; Karmila, Mila; Hariyanti, Dwi Prasetiyawati Diyah (Universitas PGRI Semarang, 2024)
AbstractThe focus of this research is to describe the implementation of religious character education at Al Azam Kindergarten Semarang, to find out the obstacles faced in implementing religious character education at Al Azam Kindergarten Semarang and to find out how to overcome the obstacles faced in implementing religious character education at Al Azam Kindergarten Semarang. This research is a descriptive study with a qualitative approach, namely an attempt to reveal a problem or situation or event as it really is so that it is simply to reveal facts. This research was conducted at Al Azam Kindergarten Semarang in connection with the implementation of religious character education. The results of this research are that the implementation of general character education at Kindergarten Al Azam Semarang is very good, in its implementation it has been designed in the vision, mission and objectives of the establishment of Kindergarten Al Azam Semarang. The methods of religious character education for Al Azam Kindergarten students in Semarang are appropriate, namely habituation, exemplary advice, attention and punishment. For the obstacles, namely lack of parental cooperation at home, children's different characters, the solution is to provide parents with information about existing programs at school, so that parents and teachers can help in nurturing children's religious character.Keywords: Character building; ReligiousAbstrakFokus penelitian ini yaitu untuk mendeskripsikan implementasi pendidikan karakter religius di TK Al Azam Semarang, untuk mengetahui kendala-kendala yang di hadapi dalam mengimplementasikan pendidikan karakter religius di TK Al Azam Semarang dan untuk mengetahui cara mengatasi kendala-kendala yang di hadapi dalam mengimplementasikan pendidikan karakter religius di TK Al Azam Semarang. Penelitian ini merupakan sebuah penelitian deskriptif dengan pendekatan kualitatif yaitu suatu usaha mengungkapkan suatu masalah atau keadaan atau peristiwa sebagaimana adanya sehingga bersifat sekedar untuk mengungkapkan fakta. Penelitian ini dilakukan di TK Al Azam Semarang pada Tahun Ajaran 2019/2020 berkaitan dengan pelaksanaan pendidikan karakter religius. Subjek dari penelitian ini meliputi kepala sekolah TK Al Azam Semarang,Â staff guru dan karyawan TK Al Azam Semarang. Hasil penelitian ini yaitu pelaksanaan pendidik karakter di TK Al Azam Semarang sangat baik, dalam pelaksanaannya sudah terancang dalam visi misi serta tujuan umum pendirian TK Al Azam Semarang. Metode-meode pendidikan karakter religius pada anak TK Al Azam Semarang sudah sesuai yaitu adanya pembiasaan, keteladanan nasihat, perhatian, dan hukuman. Untuk kendala-kendalanya yaitu kurangnya kerjasama orangtua saat di rumah, karakter anak yang berbeda-beda, solusinya perlu menginformasikaan orangtua tentang program yang ada disekolah kepada orangtua, sehingga orangtua dan guru bisa bekerjasama dalam penanaman karakter religius anak.Kata kunci: Pendidikan Karakter; Religius